Civic engagement in the wake of Katrina - Koritz, Amy, 1955-; Sanchez, George J. (New public scholarship., 2009)
This collection of essays documents the ways in which educational institutions and the arts community responded to the devastation wrought by Hurricane Katrina. While firmly rooted in concrete projects, Civic Engagement in the Wake of Katrina also addresses the larger issues raised by committed public scholarship. How can higher education institutions engage with their surrounding communities? What are the pros and cons of "asset-based" and "outreach" models of civic engagement? Is it appropriate for the private sector to play a direct role in promoting civic engagement? How does public scholarship impact traditional standards of academic evaluation? Throughout the volume, this diverse collection of essays paints a remarkably consistent and persuasive account of arts-based initiatives' ability to foster social and civic renewal